2018
DOI: 10.1002/aenm.201800794
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering of TiO2 ETL for Highly Efficient and Hysteresis‐Less Planar Perovskite Solar Cell (21.4%) with Enhanced Open‐Circuit Voltage and Stability

Abstract: Interfacial studies and band alignment engineering on the electron transport layer (ETL) play a key role for fabrication of high‐performance perovskite solar cells (PSCs). Here, an amorphous layer of SnO2 (a‐SnO2) between the TiO2 ETL and the perovskite absorber is inserted and the charge transport properties of the device are studied. The double‐layer structure of TiO2 compact layer (c‐TiO2) and a‐SnO2 ETL leads to modification of interface energetics, resulting in improved charge collection and decreased car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
197
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 287 publications
(201 citation statements)
references
References 39 publications
3
197
0
1
Order By: Relevance
“…Petrozza and co-workers demonstrated that insufficient charge extraction from the perovskite film to the ETL can be remedied using a TiO 2 /PCBM bilayer ETL, and a PCE of 17.9% was achieved. [21] Numerous other efforts have been undertaken to enhance the performance of PSCs with bilayer ETLs, such as SnO 2 @TiO 2 , [22] SnO 2 /PCBM, [23] An electron-transport layer (ETL) with appropriate energy alignment and enhanced charge transfer is critical for perovskite solar cells (PSCs [24] TiO 2 /In 2 O 3 , [25] MgO/TiO 2 , [17] TiO 2 /ZnO, [26] and ZrO 2 /TiO 2 . [21] Numerous other efforts have been undertaken to enhance the performance of PSCs with bilayer ETLs, such as SnO 2 @TiO 2 , [22] SnO 2 /PCBM, [23] An electron-transport layer (ETL) with appropriate energy alignment and enhanced charge transfer is critical for perovskite solar cells (PSCs [24] TiO 2 /In 2 O 3 , [25] MgO/TiO 2 , [17] TiO 2 /ZnO, [26] and ZrO 2 /TiO 2 .…”
Section: Doi: 101002/adma201905766mentioning
confidence: 99%
See 1 more Smart Citation
“…Petrozza and co-workers demonstrated that insufficient charge extraction from the perovskite film to the ETL can be remedied using a TiO 2 /PCBM bilayer ETL, and a PCE of 17.9% was achieved. [21] Numerous other efforts have been undertaken to enhance the performance of PSCs with bilayer ETLs, such as SnO 2 @TiO 2 , [22] SnO 2 /PCBM, [23] An electron-transport layer (ETL) with appropriate energy alignment and enhanced charge transfer is critical for perovskite solar cells (PSCs [24] TiO 2 /In 2 O 3 , [25] MgO/TiO 2 , [17] TiO 2 /ZnO, [26] and ZrO 2 /TiO 2 . [21] Numerous other efforts have been undertaken to enhance the performance of PSCs with bilayer ETLs, such as SnO 2 @TiO 2 , [22] SnO 2 /PCBM, [23] An electron-transport layer (ETL) with appropriate energy alignment and enhanced charge transfer is critical for perovskite solar cells (PSCs [24] TiO 2 /In 2 O 3 , [25] MgO/TiO 2 , [17] TiO 2 /ZnO, [26] and ZrO 2 /TiO 2 .…”
Section: Doi: 101002/adma201905766mentioning
confidence: 99%
“…[16] Recently, researchers have focused on the use of bilayer ETL, [17] and the bilayer stack structure has been demonstrated to be effective for improving device efficiency. [21] Numerous other efforts have been undertaken to enhance the performance of PSCs with bilayer ETLs, such as SnO 2 @TiO 2 , [22] SnO 2 /PCBM, [23] An electron-transport layer (ETL) with appropriate energy alignment and enhanced charge transfer is critical for perovskite solar cells (PSCs). Petrozza and co-workers demonstrated that insufficient charge extraction from the perovskite film to the ETL can be remedied using a TiO 2 /PCBM bilayer ETL, and a PCE of 17.9% was achieved.…”
mentioning
confidence: 99%
“…Organic photovoltaic (OPV) devices are promising candidates for clean renewable energy harvesting, which have attracted tremendous attention from many research groups due to their application for efficient flexible solar cells and high PCE over 17% for tandem design . In order to improve efficiency of OPV devices for commercial applications, a number of strategies can be employed, such as material development, interface and morphology optimization, or architectural engineering . Polymer semiconductors suffer from low mobilities and short diffusion lengths as compared to other types of semiconductors, which limits the active layer thickness and the light absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and co‐workers and Xue and co‐workers used ZnO/SnO 2 which suppressed interfacial charge recombination and benefit to charge extraction . Kong and co‐workers and Grätzel and co‐workers reported a TiO 2 /SnO 2 structure that adjusted the band alignment to improve V oc , and device stability . Wang and co‐workers introduced a bilayer SnO 2 by tuning F‐doping level in SnO 2 nanocrystal where they demonstrate gradient F‐doped SnO 2 can effectively decrease the band offset and result in higher V oc in the devices .…”
Section: Introductionmentioning
confidence: 99%